Borges y la potencia del lenguaje - Pablo M. Ruiz (Cuadernos LIRICO)
Unlike most other major twentieth century authors, Borges’s literary output establishes a particularly rich relationship with language. The ways in which Borges thought about language, imagined and used language, are among the most important contributions of his literature. This article, on the one hand, aims to identify a variety of ways in which Borges used language and language mechanisms in order to produce his literature. At the same time, it traces a genealogy of Borges’s fiction, or of a good part of that fiction, in relation to the reflections about language that Borges undertakes throughout his career. In order to shed some extra light on that trajectory, the article also presents as a counterpoint with the avant-gardes and their practices in relation to language, paying special attention to the connections between Borges and James Joyce.